Visual Culture Wars at the Borders of Contemporary China
XXIII, 253 p. 41 illus., 39 illus. in color.
Keywords: This edited collection brings together essays that share in a critical attention to visual culture as a means of representing, contributing to and/or intervening with discursive struggles and territorial conflicts currently taking place at and across the outward-facing and internal borders of the People’s Republic of China. Elucidated by the essays collected here for the first time is a constellation of what might be described as visual culture wars comprising resistances on numerous fronts not only to the growing power and expansiveness of the Chinese state but also the residues of a once pervasively suppressive Western colonialism/imperialism. The present volume addresses visual culture related to struggles and conflicts at the borders of Hong Kong, the South China Sea and Taiwan as well within the PRC with regard the so-called “Great Firewall of China” and differences in discursive outlook between China and the West on the significances of art, technology, gender and sexuality. In doing so, it provides a vital index of twenty-first century China’s diversely conflicted status as a contemporary nation-state and arguably nascent empire.